Identification of resveratrol oligomers as inhibitors of cystic fibrosis transmembrane conductance regulator by high-throughput screening of natural products from chinese medicinal plants. - Yaofang Zhang; Bo Yu; Yujie Sui; Xin Gao; Hong Yang; Tonghui Ma (PLoS ONE)
Inhibitors of cystic fibrosis transmembrane conductance regulator (CFTR) have been widely used for characterizing CFTR function in epithelial fluid transport and in diseases such as secretory diarrhea, polycystic kidney disease and cystic fibrosis. Few small molecule CFTR inhibitors have been discovered so far from combinatorial compound library. In the present study, we used a high throughput screening (HTS)-based natural product discovery strategy to identify new CFTR inhibitors from Chinese medicinal herbs. By screening 40,000 small molecule fractions from 500 herbal plants, we identified 42 positive fractions from 5 herbs and isolated two compounds that inhibited CFTR conductance from Chinese wild grapevine (Vitis amurensis Rupr). Mass spectrometry (MS) and nuclear magnetic resonance (NMR) studies determined the two active compounds as trans-ε-viniferin (TV) and r-2-viniferin (RV), respectively. Both compounds dose-dependently blocked CFTR-mediated iodide influx with IC50 around 20 μM. Further analysis by excised inside-out patch-clamp indicated strong inhibition of protein kinase A (PKA)-activated CFTR chloride currents by TV and RV. In ex vivo studies, TV and RV inhibited CFTR-mediated short-circuit Cl- currents in isolated rat colonic mucosa in a dose-dependent manner. In a closed-loop mouse model, intraluminal applications of TV (2.5 μg) and RV (4.5 μg) significantly reduced cholera toxin-induced intestinal fluid secretion. The present study identified two resveratrol oligomers as new CFTR inhibitors and validates our high-throughput screening method for discovery of bioactive compounds from natural products with complex chemical ingredients such as herbal plants.